Polymeric flavonoids processed with co-polymers as UV and thermal stabilisers for polyethylene films. (December 2015) - Bridson, James H.; Kaur, Jasneet; Zhang, Zhenhua; Donaldson, Lloyd; Fernyhough, Alan
Abstract: Stabilisers are often required to extend the service life of polymers, however few bio-based options are available. The effect of polymeric flavonoids, processed with co-polymers, on the thermal and UV stability of polyethylene films was investigated. Condensed tannin extracts from Pinus radiata and Acacia mearnsii were compounded with a range of co-polymers into linear low density polyethylene films. Tannin compatibility with the polymer matrix was studied using confocal microscopy. The thermal and UV stability was assessed using differential scanning calorimetry, accelerated weathering, mechanical testing and infrared spectroscopy. Tannin increased the thermo-oxidative stability of the films, particularly when the compatibility was enhanced using co-polymers. Furthermore, tannin improved the UV stability during accelerated weathering, with greater strength and elongation retention. The stability provided by tannin may be attributed to radical scavenging by the chain breaking donor mechanism. These results show potential for tannin as a stabiliser for polyethylene, however further improvements in performance need to be achieved to facilitate commercial uptake.